Effect of a heat stress episode on feed and water intake in dairy goats bred under temperate climate - Giger-Reverdin S.; Jaber L.; Tessier J.; Duvaux-Ponter C. (Feeding and management strategies to improve livestock productivity, welfare and product quality under climate change, 2013)
The effect of a heat stress episode was studied in eight dairy goats bred under temperate climate with ad libitum access to water. The increase in temperature from 19 to 28°C (recorded at 5 pm) modified neither feed intake nor the global shapes of feed and water intake patterns. However, there was a 40% increase in water intake and the latency from the beginning of the afternoon meal to the first water intake decreased from 35 to 26 min. Blood PCO2 decreased because the animals hyperventilated to reduce their body temperature, whereas rectal temperature increased by around 0.6°C. Milk production was not modified, but milk fat content decreased. A significant goat effect was observed for almost all the results. Goats from the Alpine breed drunk more water when expressed on a dry matter intake basis than those from the Saanen breed. This could be explained either by their higher level of feed intake which enhanced the post-prandial heat production or by the difference in latent heat dissipated through sweating linked to coat colour.
14. International Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2012/06/15-17, Hammamet (Tunisia)